P37 BTK inhibitor Ibrutinib regulates the TLR3 induced IL-1ß expression in HNSCC. Issue 5 (May 2015) - Lanka, A.; Pries, R.; Wollenberg, B.
Abstract : Introduction: Ibrutinib is the first drug designed to inhibit Burton's tyrosine kinase (BTK) activity. It is a new targeted therapy for chronic lymphocytic leukemia (CLL). BTK plays a critical role in humoral immune responses and is essential mediator for the growth and survival of B-Cells. Several unknown underlying immunosuppressive mechanisms are involved in the development of Head and Neck Squamous Cell Carcinomas (HNSCCs) worldwide. Material and methods: To investigate how the BTK inhibitor Ibrutinib influences the progression and microenvironment biosynthesis in HNSCC, different established HNSCC cell lines were treated with Ibrutinib and triggered with the TLR3 ligand Polyinosinic:polycytidylic acid (PolyI:C) through both extracellular and intracellular ways. Results: This resulted in reduced expression levels of immunomodulatory cytokines IL-1 β and IL-8. Furthermore, our data demonstrate an efficient suppression of the extracellular-signal regulated kinase1/2 (ERK1/2) MAPK as well as significantly reduced cell viability. Conclusion: Therefore, Ibrutinib could be a new and promising approach to unfold the underlying immunosuppressive mechanisms involved in HNSCC.